Rekayasa upper sandal flatbed dari limbah kain polyester (Studi kasus: Hijack Sandals) - Nugroho, Muhamad Agung; Waskito, Mohamad Arif (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2025)
This research addresses the challenge of fabric waste in sandal production caused by high market demand. The study's primary contribution is demonstrating an effective method for repurposing production waste fabric into marketable flatbed sandals, reducing environmental impact while maintaining industry quality standards. Through experimental design, we identified opportunities to transform waste materials into consumer products, potentially creating new market segments responsive to current trends and preferences. Implementation of this approach reduced fabric waste by one 40x60cm trashbag per sandal product. This research provides a sustainable solution to material waste in the footwear industry by creating value from production residuals, simultaneously addressing environmental concerns and opening new commercial possibilities in the consumer footwear market.